How the Division of Upper Silesia Impacted the Financial Condition of “Brackie” Insurance in the Years 1922–1926 - Danowska-Prokop, Barbara (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2023)
Objective: The article shows the impact of the division of the Upper Silesian plebiscite area on the financial condition of mining “brackie” insurance in a Silesian Voivodeship in the years 1922–1926.Research Design & Methods: An analysis of source materials and description are the main methods used in the article.Findings: In the Polish part of Upper Silesia, in the interwar period, two social insurance systems operated in parallel in the coal mining industry: universal and compulsory social insurance, and voluntary professional mining insurance (“brackie” insurance). The insurance dualism was brought about not only by economic but also legal, political and social factors.Implications / Recommendations: Insurance offered benefits tailored both to working conditions and to the specific health and salary needs of Upper Silesian miners. In addition, they guaranteed social and political peace.Contribution: The analysis may become part of a larger research project showing the relationship between industrialisation and the social security system.